Dividend signaling and bank payouts in the Great Financial Crisis - Ragnar Enger Juelsrud; Plamen T. Nenov (Norges Bank, 2022)
We study the dividend payouts of U.S. banks during the 2008 financial crisis. Using a difference-in-differences methodology, we shows that banks with higher share of short-term liabilities to total liabilities, which were thus more exposed to the rollover crisis that took place in 2008, increased their dividend payouts relative to less exposed banks. This relative increase in dividend payouts is concentrated in relatively cash-rich banks. The dividend payout increase was associated with a short-run increase in stock valuations. We argue that this front-loading of dividends of more exposed banks is consistent with a theory of dividend payouts, in which the payout policy has a (short-run) stabilizing role on the bank's liquidity position by signaling information to short-term lenders about the bank's available liquidity.
hdl:11250/3031785
Keywords: G01; G21; G35; 330; payout policies; dividend signaling; rollover crises; bank runs; liquidity crises